New policy baseline assessment methodology to conduct food policy analysis - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
This methodology was previously applied in Bangladesh and report was finalized. By the end of 2019, the methodology had been applied in Vietnam (finalized) and in Nigeria (not yet finalized). In 2020, we plan to apply it in Ethiopia. Reports available upon request. Please contact a.wyatt@cgiar.org for access.